H i discs of L[ast] galaxies as probes of the baryonic physics of galaxy evolution - Gensior, Jindra; Feldmann, Robert; Reina-Campos, Marta; Trujillo-Gomez, Sebastian; Mayer, Lucio; Keller, Benjamin W; Wetzel, Andrew; Kruijssen, J M Diederik; Hopkins, Philip F; Moreno, Jorge (Monthly notices of the Royal Astronomical Society, 2024)
Understanding what shapes the cold gas component of galaxies, which both provides the fuel for star formation and is strongly affected by the subsequent stellar feedback, is a crucial step towards a better understanding of galaxy evolution. Here, we analyse the H i properties of a sample of 46 Milky Way halo-mass galaxies, drawn from cosmological simulations (EMP-Pathfinder and Firebox). This set of simulations comprises galaxies evolved self-consistently across cosmic time with different baryonic sub-grid physics: three different star formation models [constant star formation efficiency (SFE) with different star formation eligibility criteria, and an environmentally dependent, turbulence-based SFE] and two different feedback prescriptions, where only one sub-sample includes early stellar feedback. We use these simulations to assess the impact of different baryonic physics on the H i content of galaxies. We find that the galaxy-wide H i properties agree with each other and with observations. However, differences appear for small-scale properties. The thin H i discs observed in the local universe are only reproduced with a turbulence-dependent SFE and/or early stellar feedback. Furthermore, we find that the morphology of H i discs is particularly sensitive to the different physics models: galaxies simulated with a turbulence-based SFE have discs that are smoother and more rotationally symmetric, compared to those simulated with a constant SFE; galaxies simulated with early stellar feedback have more regular discs than supernova-feedback-only galaxies. We find that the rotational asymmetry of the H i discs depends most strongly on the underlying physics model, making this a promising observable for understanding the physics responsible for shaping the interstellar medium of galaxies.